GOLD PAWN PRODUCTS, PROMOTION, PERCEIVED EASE OF ACCESS, AND CUSTOMER LOYALTY AT PEGADAIAN SUMBAWA - Tegar Firman Satriawan; Reza Muhammad Rizqi (UPT Publikasi Ilmiah UNISBA, 2026)
This study investigates how Gold Pawn Products, Promotion Strategy, and Perceived Ease of Access shape Customer Loyalty at Pegadaian Sumbawa. The study responds to a theoretical gap in financial services marketing by integrating product-based service quality, Integrated Marketing Communication, and the Technology Acceptance Model into a unified loyalty framework for gold pawn services in a local, semi-urban market. A quantitative causal design was applied to 100 active customers who were selected through purposive sampling based on age eligibility and repeated gold pawn transactions. Data were analyzed using Structural Equation Modeling-Partial Least Squares with SmartPLS 3.0 through measurement model testing, structural model evaluation, and bootstrapping with 5,000 resamples. The results show that Gold Pawn Products, Promotion Strategy, and Perceived Ease of Access have positive and significant effects on Customer Loyalty. Perceived Ease of Access has the strongest path coefficient, followed by Gold Pawn Products and Promotion Strategy, while the model explains 61.3% of the variance in Customer Loyalty. Theoretically, the findings demonstrate that loyalty in pawnbroking services emerges from the interaction between core product value, persuasive communication, and frictionless service access. Practically, Pegadaian Sumbawa should strengthen transparent gold valuation, targeted digital promotion, and hybrid service accessibility to retain customers amid increasing competition from digital and non-bank financial alternatives.